Evaluation of Sectoral Credit Performances of Metropolitan Municipalities in Turkey Using The CRITIC-CODAS Method (2014 and 2024) (Third Sector Social Economic Review, 2025)
This study aims to comparatively analyze the sectoral credit performance of metropolitan cities in Turkey between 2014 and 2024. Regional disparities in credit allocation, sectoral credit risks, and repayment performance constitute the main areas of analysis. For this purpose, 15 criteria were identified; their weights were calculated using the CRITIC method, and the credit performance rankings were obtained through the CODAS method. The findings reveal that provinces with strong financial structures, such as Istanbul, Ankara, and Kocaeli, demonstrate high performance, while Mardin, Şanlıurfa, and Diyarbakır remain weak. Moreover, while stable performance was observed in industry and production sectors, increasing risks were identified in construction and personal loan categories. The results indicate that credit allocation policies should be redesigned by taking regional disparities into account. The study provides policymakers and the banking sector with data-driven strategic recommendations to enhance financial stability.
Keywords: Credit Performance; Regional Disparities; CRITIC Method; CODAS Method; Credit Risk